Inflammatory proteins are associated with mortality in a middle‐aged diverse cohort - Nicole Noren Hooten; Nicolle A. Mode; Samuel Allotey; Ngozi Ezike; Alan B. Zonderman; Michele K. Evans (Clinical and Translational Medicine, 2023)
Abstract Background Recent data indicate a decline in overall longevity in the United States. Even prior to the COVID‐19 pandemic, an increase in midlife mortality rates had been reported. Life expectancy disparities have persisted in the United States for racial and ethnic groups and for individuals living at low socioeconomic status. These continued trends in mortality indicate the importance of examining biomarkers of mortality at midlife in at‐risk populations. Circulating levels of cytokines and inflammatory markers reflect systemic chronic inflammation, which is a well‐known driver of many age‐related diseases. Methods In this study, we examined the relationship of nine different inflammatory proteins with mortality in a middle‐aged socioeconomically diverse cohort of African–American and White men and women (n = 1122; mean age = 47.8 years). Results We found significant differences in inflammatory‐related protein serum levels between African–American and White middle‐aged adults. E‐selectin and fibrinogen were significantly higher in African–American adults. IFN‐γ, TNF‐α trimer, monocyte chemoattractant protein‐1 (MCP‐1), soluble receptor for advanced glycation end‐products (sRAGE) and P‐selectin were significantly higher in White participants compared to African–American participants. Higher levels of E‐selectin, MCP‐1 and P‐selectin were associated with a higher mortality risk. Furthermore, there was a significant interaction between sex and IL‐6 with mortality. IL‐6 levels were associated with an increased risk of mortality, an association that was significantly greater in women than men. In addition, White participants with high levels of sRAGE had significantly higher survival probability than White participants with low levels of sRAGE, while African–American participants had similar survival probabilities across sRAGE levels. Conclusions These results suggest that circulating inflammatory markers can be utilized as indicators of midlife mortality risk in a socioeconomically diverse cohort of African–American and White individuals.